Embedded Speech and the Embodied Speaker in Roman Historiography - O’Gorman, Ellen (Histos, 2023)
This paper considers the presentation of speech performance in Roman historiography. It proposes the use of media theory to analyse the different medial elements of performed speech in Roman rhetorical culture. It identifies traces of performance in written speech and how similar traces are exploited in the historian’s composition of speeches and narrative frames to speech. These traces are analysed as instances of ‘intermediality’ which help to present speech as a form of historical action. The implications of this for history as a written and a recited text are briefly reviewed.